Vascular contributions to cognitive impairment and dementia including Alzheimer's disease. Issue 6 (12th December 2014) - Snyder, Heather M.; Corriveau, Roderick A.; Craft, Suzanne; Faber, James E.; Greenberg, Steven M.; Knopman, David; Lamb, Bruce T.; Montine, Thomas J.; Nedergaard, Maiken; Schaffer, Chris B.; Schneider, Julie A.; Wellington, Cheryl; et al.
Abstract: Scientific evidence continues to demonstrate the linkage of vascular contributions to cognitive impairment and dementia such as Alzheimer's disease. In December, 2013, the Alzheimer's Association, with scientific input from the National Institute of Neurological Disorders and Stroke and the National Heart, Lung and Blood Institute from the National Institutes of Health, convened scientific experts to discuss the research gaps in our understanding of how vascular factors contribute to Alzheimer's disease and related dementia. This manuscript summarizes the meeting and the resultant discussion, including an outline of next steps needed to move this area of research forward.